A new deep-sea crustacean family of Tanaidacea is established from Aotearoa New Zealand and Southeast Australia based principally on morphology - Graham J. Bird; Magdalena Błażewicz (Scientific Reports)
Abstract We establish a new deep-sea tanaidacean family, Arthruridae n. fam., separated from the family Tanaellidae Larsen and Wilson, 2002, and based on a morphology-based phylogenetic analysis. This new taxon is supported by molecular evidence from a recent study of the newly described Caudalongidae Błażewicz & Bird 2024. Arthrurids resemble tanaellids such as Tanaella Norman & Stebbing, 1886 with their robust bodies, or Arhaphuroides Sieg, 1986 with their fused projecting uropod exopod, but also exhibit some agathotanaid-like features. These include the pereonite shape, pleon-pleotelson configuration, and pereopod morphology that are absent in the more diverse Tanaellidae, but arthrurids have a more plesiomorphic cheliped-cephalothorax articulation compared to those in the Agathotanaidae Lang, 1971. A large epignath seta, large coxal sclerite on the cephalothorax, and sticklike pereopods are among characters distinguishing the Arthruridae from most tanaellids. Two new genera are established, Arthruropsis n. gen. and Paralibanius n. gen., with the former tanaellid Arhaphuroides bombus Larsen, 2005, transferred to Arthruropsis n. gen. Six new species from bathyal New Zealand waters are described, Libanius concertator n. sp., L. intonsus n. sp., L. largitas n. sp., L. projectus n. sp., L. tangaroa n. sp., and Paralibanius taitonga n. sp., along with three from the southeastern Australia slope, Libanius australis n. sp., L. brevicarpus n. sp., and L. clisicola n. sp. We provide a key to the 13 known arthrurid species.